2017
DOI: 10.3389/fimmu.2017.00057
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Innate Antiviral Immune Response in Porcine Intestinal Epithelial Cells: Influence of Immunobiotic Lactobacilli

Abstract: Lactobacillus rhamnosus CRL1505 and Lactobacillus plantarum CRL1506 are immunobiotic strains able to increase protection against viral intestinal infections as demonstrated in animal models and humans. To gain insight into the host–immunobiotic interaction, the transcriptomic response of porcine intestinal epithelial (PIE) cells to the challenge with viral molecular associated pattern poly(I:C) and the changes in the transcriptomic profile induced by the immunobiotics strains CRL1505 and CRL1506 were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 43 publications
(62 reference statements)
8
104
0
Order By: Relevance
“…Transcriptomic studies revealed the capacity of L. rhamnosus CRL1505 to differentially modulate the innate antiviral immune response in porcine intestinal epithelial cells. Higher expression levels of type I IFNs as well as in several antiviral factors including ifit1, nlpr3, mda5, msx1, rig1 ifit2, and mx2 were found in CRL1505-treated cells when compared to control cells (23). In addition, it was demonstrated in vitro that viable L. rhamnosus CRL1505 is able to efficiently stimulate the expression of IFN-γ in porcine intestinal CD172a + CD11R1 − macrophages (22).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Transcriptomic studies revealed the capacity of L. rhamnosus CRL1505 to differentially modulate the innate antiviral immune response in porcine intestinal epithelial cells. Higher expression levels of type I IFNs as well as in several antiviral factors including ifit1, nlpr3, mda5, msx1, rig1 ifit2, and mx2 were found in CRL1505-treated cells when compared to control cells (23). In addition, it was demonstrated in vitro that viable L. rhamnosus CRL1505 is able to efficiently stimulate the expression of IFN-γ in porcine intestinal CD172a + CD11R1 − macrophages (22).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous comparative in vitro studies evaluating the ability of L. rhamnosus CRL1505 and L. plantarum CRL1506 to modulate immune responses in intestinal epithelial cells and antigen presenting cells (APCs) found significant differences between the two lactobacilli strains (22,23). It was demonstrated that intestinal epithelial cells were modulated by immunobiotic CRL1505 and CRL1506 in a strain-dependent fashion to enhance antiviral responses (23). Interestingly, L. rhamnosus CRL1505 was more efficient that L. plantarum CRL1506 to increase the expression of IFN-β and IL-6 in intestinal epithelial cells, both cytokines known to influence immune responses generated by immune cells located under the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of vaccine antigens via viable vectors not only can stimulate the intestinal immune response, but can also produce specific immune responses against specific antigens that allow the body to achieve full protection. Compared to attenuated Salmonella as mucosal antigen delivery vehicles [36][37][38], lactic acid bacteria (LAB) are more advantageous [20,22,23,30,39]. The long-term use of L. casei in the food industry has been demonstrated to be non-pathogenic, and has been designated as "generally recognized as safe".…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is a Gram-positive, facultative anaerobic or microaerophilic, rod-shaped, non-spore-forming bacteria, which is the most common probiotic found in food and the intestinal tract of humans and animals [16]. Studies have shown that some specific isolates of lactobacilli have potential immunomodulatory properties, such as promoting strong adhesive interactions with intestinal epithelial cells [17] and preventing injury of the epithelial cell barrier [18], anti-inflammatory capacity [19], modulating innate immune response [20] and sIgA production [21], regulating immunological functions of dendritic cells, and T helper cells activation [22,23]. Moreover, lactobacilli can survive transit through the upper gastrointestinal tract and colonize the intestinal tract [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro transcriptomic studies showed that Lactobacillus plantarum CRL1506 is able to modulate the expression of type I interferons (IFNs), antiviral factors, cytokines, chemokines, and adhesion molecules in porcine intestinal epithelial (PIE) cells challenged with the Toll-like receptor (TLR)-3 ligand poly(I:C) (9). In addition, studies in porcine antigen-presenting cells isolated from Peyer's patches demonstrated that the CRL1506 strain differentially modulated the expression of IFN-γ, interleukin (IL)-1β, IL-12, IL-6, and tumor necrosis factor (TNF)-α (10).…”
Section: Introductionmentioning
confidence: 99%